Profil Kemampuan Mahasiswa dalam Menyelesaikan Studi Kasus pada Mata Kuliah Filsafat IPA - Banu Kisworo (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2026)
This study aimed to describe the profile of students' analytical abilities in completing case study assignments on the topics of Global Warming and Carbon Emissions in a Philosophy of Science course. The research employed a quantitative descriptive approach involving 31 students from the Science Education Study Program. Data were collected through the assessment of case study assignments and analyzed based on four aspects: case comprehension, problem analysis, evidence-based argumentation, and communication of results. The data were analyzed using descriptive statistics, including mean scores and achievement categories. The findings revealed that the case comprehension aspect achieved the highest mean score of 90.03 (excellent), followed by problem analysis with a mean score of 80.61 (good), evidence-based argumentation with a mean score of 71.10 (good), and communication of results with a mean score of 60.19 (fair). These findings indicate that students were able to understand issues related to global warming and carbon emissions effectively; however, they still require further support in communicating their analytical findings in a systematic and argumentative manner. Case study-based learning has the potential to serve as an effective strategy for fostering students' critical and reflective thinking skills in Philosophy of Science courses.